Can I MOOC to catch up? The effects of using an LMOOC as a remedial tool for EFL students in Thailand - Jitpaisarnwattana, N; Chalmers, H (Canadian Center of Science and Education, 2021)
This study investigated the effects of supplementing a traditional EFL class with a grammar-focused LMOOC. It also investigated students’ attitudes to the LMOOC. Students taking a compulsory English course at a nursing college in Thailand were divided into two groups, a LMOOC group (n=33) and a non-LMOOC group (n=26). The LMOOC group engaged in a 4-week LMOOC as a supplement to their usual English classes. The non-LMOOC group continued with their usual English classes with no additional interventions. Final examination scores and gains since the midterm for the two groups were compared. Attitudes to the LMOOC were assessed using a questionnaire and interviews. Students in the LMOOC group experienced statistically significantly larger gains in grammar scores than the non-LMOOC group (M = 5.45, SD = 4.31, p < .001). Students reported very positive attitudes towards the LMOOC, in terms of enjoyment and perceived effectiveness. The estimated gains found in this small study were relatively modest, but our findings suggest that LMOOCs as a way to supplement in-class teaching may improve attainment and foster positive attitudes. Further controlled experiments to assess the wider applicability of our findings are needed.